2009
DOI: 10.1590/s0100-72032009000100006
|View full text |Cite|
|
Sign up to set email alerts
|

Depressão e ansiedade em mulheres climatéricas: fatores associados

Abstract: OBJETIVO: determinar a prevalência de depressão e ansiedade em mulheres climatéricas e os prováveis fatores responsáveis por sua ocorrência. MÉTODOS: em estudo transversal, foram selecionadas 93 mulheres que frequentaram um ambulatório de climatério no período de maio de 2006 a agosto de 2007. Como critério de inclusão foram consideradas mulheres na faixa etária de 40 a 65 anos e que concordaram em participar do projeto. Os critérios de exclusão foram: pacientes em uso de terapia hormonal, hormonioterapia por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
31

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 18 publications
2
20
0
31
Order By: Relevance
“…Evidence of this nature have been demonstrated in several studies that cover this topic in Brazil [13][14]. In turn, the significant number of women addressed in this study that had a fixed partner, represents a percentage consistent with other studies addressing sociodemographic factors in climacteric women [15].…”
Section: Discussionsupporting
confidence: 87%
“…Evidence of this nature have been demonstrated in several studies that cover this topic in Brazil [13][14]. In turn, the significant number of women addressed in this study that had a fixed partner, represents a percentage consistent with other studies addressing sociodemographic factors in climacteric women [15].…”
Section: Discussionsupporting
confidence: 87%
“…Em um estudo qualitativo com 28 mulheres usuárias de drogas em tratamento no Canadá, o trabalho foi observado como uma necessidade aliada ao tratamento, contribuindo assim no sentimento de pertencimento à sociedade (Kruk & Sandberg, 2013). Em um estudo brasileiro com 93 mulheres, o trabalho remunerado foi considerado fator de proteção, pois apresentou um risco cerca de cinco vezes menor de apresentar depressão (Polisseni et al, 2009).…”
Section: Discussionunclassified
“…A cohort study by a Harvard research team found that significant new depressive symptoms in menopausal women have at least twice the possibility of leading to depression than in the pre-menopausal stage [6]. Anxiety and insomnia can be predictors of depression for women in this period [7]. Anxiety can also predict vasomotor symptoms [8].…”
Section: Introductionmentioning
confidence: 99%